Наследование признаков коробочки межвидовыми гибридами F₁ льна - Поляков, В.А.; Лях, В.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. Oil flax Linum humile and annual wild species L. angustifolium, L. bienne, L. hispanicum and L. crepitans are included in n = 15 group. Wild flax species are of interest due to important valuable traits such as resistance to diseases and extreme environmental factors, increased lateral branching and early ripeness. The aim of our work was to study the inheritance of taxonomically and economically important morphological traits of the bolls in F₁ interspecific flax hybrids. Methods. F₁ interspecific hybrids between cultivated flax and L. angustifolium, L. bienne, L. hispanicum and L. crepitans were used as the experimental material. The degrees of dominance for the traits of boll diameter, boll height and boll dehiscence were calculated. The intermediate inheritance, dominance and overdominance of the traits were taking into acсount. Results. It was established that all F₁ interspecific hybrids possessed dehiscent bolls in contrast to parental cultivated lines. In hybrids with L. angustifolium, L. bienne and L. hispanicum an intermediate inheritance of boll size and dominance of boll dehiscence were observed, whereas in hybrid with L. crepitans a positive heterosis of boll diameter and boll height as well as intermediate inheritance of boll dehiscence were found. Conclusions. A various degrees of dominancecfor boll traits in interspecific hybrids involving wild flax species L. angustifolium, L. bienne and L. hispanicum as compared with L. crepitans were revealed.